The Effect of Invisible Employees on Mental Health and the Mediating Role of Communication Apprehension in Rafsanjan University of Medical Sciences - Elham Dehshiri Parizy; Malikeh Beheshtifar (Kerman University of Medical Sciences, 2020)
The Effect of Invisible Employees on Mental Health and the Mediating Role of Communication Apprehension in Rafsanjan University of Medical Sciences Dehshiri Parizy Elham1, Beheshtifar Malikeh2* 1. M.Sc. in Public Management, Department of Management, Rafsanjan Branch, Islamic Azad University, Rafsanjan, Iran 2. Associate Professor, Department  of Management, Rafsanjan Branch, Islamic Azad University, Rafsanjan, Iran *Corresponding Author: Malikeh Beheshtifar Address: Islamic Azad University, Velayat Blvd., Rafsanjan, Iran Tel: 00983431313083                                         Email: m.beheshtifar@iaurafsanjan.ac.ir Abstract: Background & Objectives: Lack of mental health as a special concern of the organizations could have distressing effects on individuals and organizations. Studies show that employee invisibility and communication apprehension could have a negative effect on mental health. The objective of this research was to investigate the effect of invisible employees on mental health based on the mediating role of communication apprehension in Rafsanjan University of Medical Sciences. Methods: This descriptive-analytical study was conducted based on a cross-sectional design in 2019 on 276 university staff who were selected by stratified random sampling. Data were collected through three questionnaires. For statistical analysis, structural equation modeling as well as SPSS software (version 23) and Amos (version 20) were used. Results: The total mean scores of invisible employees, mental health, and communication apprehension variables were 2.22, 3.55, and 2.47, respectively. The invisible employees variable had no effect on mental health (path coefficient = -0.100, P =0.117), however, it had a direct effect on communication apprehension (path coefficient = 0.743, P =0.001). Moreover, communication apprehension had a negative effect on mental health (path coefficient = -0.881, P =0.001). Conclusion: To promote mental health, university managers must consider effective communication between employees in the workplace. Furthermore, in order to reduce invisible employees, managers must value them, not ignore them in the workplace, use their experience in various tasks, and appreciate their efforts.   Keywords: Invisible Employees, Mental Health, Communication, Apprehension staff   Citation: Dehshiri Parizy E, Beheshtifar M. The Effect of Invisible Employees on Mental Health and the Mediating Role of Communication Apprehension in Rafsanjan University of Medical Sciences. Journal of Health Based Research 2020; 5(4): 395-409. [In Persian]